(untitled) (Innovative Applications of AI, 2024)
Based on the cities of the Guangdong-Hong Kong-Macao Greater Bay Area as fundamental nodes, this study collects data from the Web of Science (WoS) with research themes including information technology, life sciences, biological sciences, and physical sciences. It constructs three regional academic cooperation complex networks from a multi-regional perspective and provides development strategies and suggestions to promote academic cooperation in the Greater Bay Area based on the analysis results. By using indicators such as degree distribution, PageRank, average path length of the network, and closeness centrality, this study analyzes the academic cooperation situation in the Guangdong-Hong Kong-Macao Greater Bay Area and identifies the influencing factors of academic cooperation in the Greater Bay Area, including culture, scientific research, economy, and population, based on the regional innovation theory framework. The study finds that the academic cooperation network of the cities in the Guangdong-Hong Kong-Macao Greater Bay Area shows a clear structure of core-periphery and has small-world characteristics. Guangzhou, Hong Kong, and Shenzhen are the cores of academic cooperation in the Greater Bay Area. Guangzhou leads Shenzhen in domestic cooperation, while Shenzhen slightly outperforms Guangzhou in international cooperation. It is also found that geographical distance is no longer a factor hindering academic cooperation.